Corporate Information Strategy and Management: The Challenges of Managing in a Network Economy - M. Applegate Lynda (MC Graw Hill, 2002)
Corporate Information Strategy and Management: The Challenges of Managing in the Internet Age, 6/E is written for students and managers who desire an overview of contemporary information systems technology (IT) management. It explains the relevant issues of effective management of information services activities and highlights the areas of greatest potential application of the technology. No assumptions are made concerning the reader’s experience with IT, but it is assumed that the reader has some course work or work experience in administration or management. It is a paperback derivative product that contains the same text portion found in Corporate Information Strategy and Management: Text and Cases, 6/e, but without the Harvard cases.